Antibacterial efficacy of Mimosa Pudica (Lajavanti) against streptococcus mutans - Swati V Balsaraf; Revant H Chole (Wolters Kluwer Medknow Publications, 2014)
Introduction: The Mimosa pudica plant also known as "touch me not" plant, "shame" plant or laajvanti is a widely grown perennial herb as a show plant because of the mysterious action of its leaves which closes when touched. Mimosa pudica is also known for various medicinal purposes such as treatment of depression, piles, insomnia and many more. It has also been used for dental purposes. Literature shows evidence of its use for dental decay, bleeding gums throughout India and worldwide. Materials and Methods: Mimosa pudica plant whole aqueous extract in 10%, 20% and 5% concentration, chlorhexidine mouth wash as control, Streptococcus mutans (Microbial Type Culture Collection). Using agar well method the efficacy of Mimosa pudica extract was tested. Results: The plant extract couldn't show efficacy as the microorganisms didn't show any growth. Conclusion: The potential of this drug needs further investigation.